2020
DOI: 10.1159/000508376
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 Index of 55% Distinguishes Two Groups of Bronchopulmonary Pure and Composite Large Cell Neuroendocrine Carcinomas with Distinct Prognosis

Abstract: Background: Little information is available concerning prognostic factors for bronchopulmonary large cell neuroendocrine carcinomas (BP-LCNECs) and even less is known about combined LCNECs (Co-LCNECs). We investigated whether an integrated morphological, immunohistochemical, and molecular approach could be used for their prognostic evaluation. Methods: Morphological (including combined features), proliferative (mitotic count/Ki-67 index), immunohistochemical (napsin A, p40, TTF-1, CD44, OTP, SSTR2A, SSTR5, mAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 50 publications
(76 reference statements)
1
25
0
1
Order By: Relevance
“…Other groups also addressed a proliferation index detected by Ki-67 IHC for stratification of LCNEC. Milione et al reported that LCNECs with co-mutation of TP53 and RB1 (SCLC-like) were significantly enriched in cases with a Ki-67 ≧55%, while the tumors with KRAS mutations were enriched in cases with Ki-67 <55% (39). Such findings along with molecular data suggest that there is an overlap between the two subtypes of LCNEC, and proliferation alone cannot predict genomic features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other groups also addressed a proliferation index detected by Ki-67 IHC for stratification of LCNEC. Milione et al reported that LCNECs with co-mutation of TP53 and RB1 (SCLC-like) were significantly enriched in cases with a Ki-67 ≧55%, while the tumors with KRAS mutations were enriched in cases with Ki-67 <55% (39). Such findings along with molecular data suggest that there is an overlap between the two subtypes of LCNEC, and proliferation alone cannot predict genomic features.…”
Section: Discussionmentioning
confidence: 99%
“…The common molecular alterations are shown in Table 2. Among tumor suppressor genes altered in LCNEC, the TP53 mutation is the most common (64-92%), followed by the RB1 mutation (19-42%) (Table 2) (8,9,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Molecular Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…ACs and LCNECs are recognized to show borderline characteristics. Increasingly, papers have reported that subgroups of LCNECs may show low proliferation activity given by a low mitotic number or Ki−67 index and share morphological characteristics of carcinoids that are in fact in a gray area for classification [ 46 , 47 ]. Moreover, recent work carried out by Alcala et al [ 48 ] showed that the separation between NETs and LCNECs might be more subtle than initially thought and identified a subgroup of ACs, named supra-carcinoids, that has carcinoid-like morphological pattern but with molecular characteristics similar to LCNECs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ki67 proliferation index has proven to be a useful parameter, at least in two different practical settings. First, on small biopsies with crash artifacts impairing the morphological evaluation, Ki67 may have paramount diagnostic value in distinguishing a NET (carcinoid) from a NEC (LCNEC or SmCLC) [35][36][37][38][39]. Second, Ki67 proliferation index has been shown to be a relevant prognostic factor in lung NETs (carcinoids) and its evaluation should be added to the pathological report, even if no agreement has been reached, until now, neither on the cut-off levels, nor on the possible integration with morphological parameters in a grading system similar to that of digestive NENs [40].…”
Section: Lungmentioning
confidence: 99%